Biological Characteristics and Clinical Significance of Soluble PD-1/PD-L1 and Exosomal PD-L1 in Cancer - Niu, Mengke; Liu, Yiming; Yi, Ming; Jiao, Dechao; Wu, Kongming (Frontiers in Immunology, 2022)
The immune checkpoint pathway consisting of the cell membrane-bound molecule programmed death protein 1 (PD-1) and its ligand PD-L1 has been found to mediate negative regulatory signals that effectively inhibit T-cell proliferation and function and impair antitumor immune responses. Considerable evidence suggests that the PD-1/PD-L1 pathway is responsible for tumor immune tolerance and immune escape. Blockage of this pathway has been found to reverse T lymphocyte depletion and restore antitumor immunity. Antagonists targeting this pathway have shown significant clinical activity in specific cancer types. Although originally identified as membrane-type molecules, several other forms of PD-1/PD-L1 have been detected in the blood of cancer patients, including soluble PD-1/PD-L1 (sPD-1/sPD-L1) and exosomal PD-L1 (exoPD-L1), increasing the composition and functional complications of the PD-1/PD-L1 signaling pathway. For example, sPD-1 has been shown to block the PD-1/PD-L immunosuppressive pathway by binding to PD-L1 and PD-L2, whereas the role of sPD-L1 and its mechanism of action in cancer remain unclear. In addition, many studies have investigated the roles of exoPD-L1 in immunosuppression, as a biomarker for tumor progression and as a predictive biomarker for response to immunotherapy. This review describes the molecular mechanisms underlying the generation of sPD-1/sPD-L1 and exoPD-L1, along with their biological activities and methods of detection. In addition, this review discusses the clinical importance of sPD-1/sPD-L1 and exoPD-L1 in cancer, including their predictive and prognostic roles and the effects of treatments that target these molecules.